2016
DOI: 10.1038/srep36280
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Susceptibility of Klebsiella pneumoniae from Community Settings in Taiwan, a Trend Analysis

Abstract: Drug-resistant Klebsiella pneumoniae, especially extended-spectrum β-lactamase (ESBL)- and/or AmpC β-lactamase-producing strains, is an emerging problem worldwide. However, few data focusing on drug susceptibility of K. pneumoniae from community is available. In this study, we analyzed 1016 K. pneumoniae isolates from outpatients or those visiting emergency rooms collected during 2002–2012 from Taiwan Surveillance of Antimicrobial Resistance program. Significantly decreased susceptibilities to 3rd generation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 53 publications
(59 reference statements)
3
31
2
3
Order By: Relevance
“…Few studies have examined this trend specifically in these resistant bacteria; however, a similar trend for increasing resistance of general K . pneumoniae isolates was found in national surveillance studies from Taiwan 34 and Korea 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined this trend specifically in these resistant bacteria; however, a similar trend for increasing resistance of general K . pneumoniae isolates was found in national surveillance studies from Taiwan 34 and Korea 35 .…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumonia was resistant only to a single antibiotic (gentamicin). Contrary to this study, extended-spectrum β-lactamase producing strains of Klebsiella pneumoniae have been shown to cause resistance to many antibiotics [22,23]. P. aeruginosa showed resistance to 3 antibiotics and intermediate to two antibiotics making it the least susceptible microorganism in the hospital surfaces.…”
Section: Discussionmentioning
confidence: 74%
“…cereus. None of the bacterial endophytes had antibacterial activity against K. pneumoniae; this could be due to the resistance mechanism by K. pneumoniae such as development of extended-spectrum β-lactamases (ESBLs) (Carlet, 2012;Lin et al, 2016). The ANOVA statistics analysis indicated that p value was less than 0.05 (p <0.05), therefore there was a significant difference between all five bacterial endophytes antimicrobial activity.…”
Section: Antibacterial Activity Of Endophytes Extracts Against Pathogmentioning
confidence: 99%